Iteration Coupling Simulation of Random Waves and Wave-Induced Currents - Jinhai Zheng; Tianwen Wang; Gang Wang; Chenming Zhang; Chi Zhang (Journal of Applied Mathematics)
A two-way coupling algorithm for wave-current interaction is developed and implemented into a nearshore circulation model to investigate the effects of fully wave-current interaction on irregular wave transformation over an elliptic shoal. The wave field is simulated by a spectral wave model WABED, and the wave-induced current is solved by a quasi-three-dimensional model WINCM. The surface roller effects are represented in the formulation of surface stress, and the roller characteristics are solved by a roller evolution model. The proposed two-way coupling algorithm can describe both the generation of wave-induced current and the current-induced wave transformation, which is more physically reasonable than the one-way approaches. The model test with a laboratory experiment shows that wave-induced currents have an important influence on the wave transformation, for example, the wave energy defocusing due to the strong jet-like current along the centerline of the shoal. It is revealed that the accuracy of simulated wave field can be significantly improved by taking into account the two-way wave-current interaction.